Influence of Interferon-γ on Salmonella Typhi Induced Macrophage Apoptosis - I, Fidan; E, Yesilyurt; A, Kalkanci; B, Erdal; FC, Gurelik; T, Imir (IIUM Medical Journal Malaysia, 2010)
Introduction: Salmonella Typhi (S.Typhi), which causes typhoid fever, is a widespread pathogen in developing countries. Interferon-gamma (IFN-γ) is a critical cytokine in host defense against Salmonella infection. IFN-γ provides protection against Salmonella infection by inducing macrophage activation. This study was designed to determine the effect of recombinant IFN-γ (rIFN-γ) on S.Typhi induced macrophage apoptosis and to examine the effect of rIFN-g on caspase-1 expression during apoptosis. Materials and Methods: After isolation of macrophages, apoptotic cells were analyzed using both annexin V-FITC detection kit by fl ow cytometry and TUNEL technique. Caspase-1 expression was determined by RT-PCR. Results: The rIFN-γ concentrations of 100 IU/ml ve 1000 IU/ml decreased macrophage apoptosis caused by S.Typhi, 13.1 % and 6.3 % respectively. Conclusion: Consequently, we observed that rIFN-g decreased Salmonella-induced apoptosis and inhibited caspase-1 expression during apoptosis. It is considered that the modulatory effect of IFN-γ on macrophage apoptosis may impact a protective effect during Salmonella infection and this may help to abort invasive S.Typhi infections.